PENGARUH BRAND COMMUNITY DAN KUALITAS PRODUK TERHADAP WORD OF MOUTH DENGAN KEPUASAN SEBAGAI VARIABEL INTERVENING (Studi pada Komunitas Yamaha V-ixion Club Indonesia di Sidoarjo) - RAHADIANSYAH, ADIMAS (Jurnal Ilmu Manajemen (JIM), 2017)
Purpose of this study is to analyze and discuss the influence of brand community and product quality of the WOM ( Word Of Mouth ) through satisfied as an intervening variable. This research is a research kausal that kind of research conclusively analyzed quantitatively, Respondents in this study are members of the community who owns and uses a Yamaha V-Ixion. Using Yamaha V-Ixion more than 6 months and has been active in events or forums for approximately 6 months of membership. By the age limit 17 years of age (for age are considered an adult and have a sim). The sampling method usimg non-probability sampling and saturated sampling is used for sampling techniques. Sample is using 100 people. Data collection techniques used in this study was a questionnaire, while data analysis using path analysis with AMOS program. The results of this study that the brand community and quality of products significantly influence satisfaction and a positive influence on WOM ( Word Of Mouth ) .The results also indicate that the testmediation brand community and product quality to the WOM ( Word Of Mouth ) through satisfied partially proven. Keywords: Brand Community, Quality Products, WOM ( Word Of Mouth ) , Satisfaction